Hybrid Swarming Algorithm With Van Der Waals Force - Yi, Zhang; Hongda, Yu; Mengdi, Sun; Yong, Xu (Frontiers in Bioengineering and Biotechnology, 2022)
This paper proposes a hybrid swarming algorithm named VPACO, which mix Ant Colony Optimization and Physarum Polycephalum Algorithm (PACO) based on Van Der Waals force. Van Der Waals force is applied to the pheromone update mechanism of the Ant Colony Optimization. (VPACO) improves the accuracy of the solution and improves the iteration speed of the algorithm compared with the original improved PACO algorithm. Simulation results have shown that the proposed approach has a higher coverage rate, more uniform configuration, and average convergence time are better than PACO and ACO. In addition, taking the capitals of 35 Asian countries as an example, the robustness and versatility of VPACO are once again verified.